Late post-traumatic epistaxis in patient with fibromuscular dysplasia - A case report - Nobre, Ana Rita (2012)
Epistaxis is a very common problem that, in most cases, is of easy control. When it occurs after head trauma, usually happens due to nasal mucosa lacerations or lesion of anterior ethmoidal or sphenopalatine artery branches. Very excepcionally, the bleeding can be so serious and of so difficult management and control that threatens patient´s life. In these situations it is mandatory to investigate and treat vascular abnormalities, specifically aneurysms, pseudoaneurysms or arteriovenous fistulas, even being rare causes of epistaxis. The authors present a case of fibromuscular dysplasia with several pseudoaneurysms diagnosed after a late posttraumatic massive epistaxis, in a 27-year-old patient , victim of a head trauma, which management of the bleeding was extremely difficult and just achieved with arteriography and embolization.